The Implementation of Participatory Action Research (PAR) to Enhance Basic Iqro' Reading Skills among Children in Alue Buloh Village - Rauzatul Jannah; M. Rezki Andhika; Suharman; Nacsiatul Fadhila (Community Development Journal, 2025)
This community service initiative was implemented at Balee Carong in Alue Buloh Village, an isolated rural community experiencing significant educational access limitations due to damaged bridge infrastructure. The geographical constraints had severely restricted children's opportunities for supplementary education, including tutoring programs and religious studies. The program aimed to enhance children's fundamental skills in Iqro' reading, memorization of short surahs and daily prayers, along with basic literacy and numeracy competencies through participatory and engaging learning methodologies. Employing Participatory Action Research (PAR) as its foundational framework, the project positioned university students as both facilitators and collaborative change agents working directly with the community. Over a 45-day implementation period, educational activities were delivered through interactive approaches including game-based learning, singing, storytelling, and various creative exercises tailored to local context. Implementation results demonstrated remarkable progress in both religious and academic dimensions among participating children. Quantitative and qualitative assessments revealed that the majority of children showed substantial advancement in Iqro' reading proficiency, with significant increases in memorization of Islamic prayers and short chapters from the Quran. Concurrently, participants exhibited marked improvement in basic reading, writing, and arithmetic capabilities. The program culminated in two significant closing events: a "Festival Anak Sholeh" (Righteous Children's Festival) serving as a comprehensive evaluation platform where children demonstrated their acquired knowledge, and an educational field trip designed as both a recreational activity and cultural enrichment experience. These outcomes substantiate that the PAR methodology, when implemented through emotional engagement strategies, active community participation, and enjoyable pedagogical techniques, effectively enhances educational quality for children in underserved remote areas. The study offers valuable insights for educational practitioners and policymakers seeking to address educational disparities in isolated communities through contextually appropriate interventions.